Chylous ascites after pedicled transverse rectus abdominis myocutaneous flap harvest. Issue 4 (3rd July 2016) - Lin, Chin-Ta; Chen, Tim-Mo
Abstract: Chylous ascites is a rare clinical condition that occurs as a consequence of disruption of the abdominal lymphatics. Here, we present the case of a 58-year-old woman with sustained chylous ascites after pedicled transverse rectus abdominis myocutaneous (TRAM) flap harvest. The chylous ascites did not decrease despite conservative therapy. For the diagnosis and localization of the chyle leakage, lymphangiography with lipiodol delivery was performed. Chylous drainage continued in a decreasing manner for the next 4 d because lipiodol accumulated to the point of leakage outside the lymphatic vessel causing a regional inflammatory reaction and obstructing the lymphatic vessels. To our knowledge, there is no case of chylous ascites related to pedicled TRAM flap harvest that has been reported in the English literature, in which the chyle leakage spontaneously resolved after lymphangiography.